The Wesleyan Methodist Church in the Transvaal, 1823-1902,The Methodist Church in the Transvaal during the 19th Century - Veysie, Donald Clifford (Rhodes University, Faculty of Divinity, Department of Divinity, 1971)
From Preface: A preliminary survey of the history of the Wesleyan Methodist Church in the Transvaal revealed that the period of the early missions, before the formation of the Transvaal and Swaziland District, required research into the documents of other Districts for the purpose of writing a detailed history. It was therefore decided to confine research to the Documents of the Transvaal and Swaziland District and to write introductory chapters on the period of the early missions. The detailed research for this dissertation begins, therefore, with the creation of the Transvaal and Swaziland District in 1880. The natural point at which to finish appeared, at first, to be the beginning of the Second Transvaal War of Independence, but further research indicated that it would be more useful to conclude with the end of the war in 1902.
Keywords: Methodist Church of Southern Africa; Methodist Church of Southern Africa -- History; Transvaal (South Africa) -- History -- To 1880; Transvaal (South Africa) -- History -- 1880-1910